The Experiences of Women in Conflict Situations and Crises: A Glimpse into Edify Yakusak’s After They Left and Helon Habila’s Chibok Girls: The Boko Haram Kidnappings and the Islamist Militancy in Nigeria - Abdulkarim, Zainab (KIU Interdisciplinary Journal of Humanities and Social Sciences, 2025)
Women in conflict zones often face heightened risks of gender-based violence, including rape, abduction, and forced marriages. Conflicts often result in the displacement of populations. Women and children are particularly vulnerable during these migrations, facing precarious living conditions in refugee camps or as internally displaced persons. Writings from Northern Nigerian provide an essential glimpse into the multifaceted experiences of women in conflict situations and crises. These writers discuss the intersection of cultural expectations and the realities of living through conflict, offering a nuanced view of societal change. Some writers from Northern Nigeria often depict the psychological and physical trauma that women endure in such environments. They also highlight the loss of home, family members, and community, emphasizing the emotional and social toll of displacement. This research will analyze Helon Habila’s Chibok Girls and Edify Yakusak’s After They. A qualitative methodological approach to research is used. It provides a method that encompasses a technique of knowledge generation through content analysis that allows the researcher to have direct contact with the subject of study with a view to making critical assessment and understanding. These narratives explore how disruptions lead to both challenges and opportunities for redefining women roles in society. Through their writings, they provide a voice to the voiceless, bringing international attention to their plight and advocating for peace and justice. These narratives not only document the suffering and challenges faced but also celebrate the strength, resilience, and enduring spirit of women. By giving voice to their stories, they contribute to a broader understanding and awareness of the impacts of conflict on women and advocate for change and empowerment.